Recent Progress in the Methodologies to Identify Physiological Ligands of Siglecs - Jiang, Huei-Syuan; Zhuang, Shao-Chien; Lam, Chak Hin; Chang, Lan-Yi; Angata, Takashi (Frontiers in Immunology, 2021)
Siglecs, a family of receptor-like lectins, recognize glycoproteins and/or glycolipids containing sialic acid in the extracellular space and transduce intracellular signaling. Recently, researchers uncovered significant contributions of Siglecs in cancer immunity, renewing interest in this family of proteins. Previous extensive studies have defined how Siglecs recognize glycan epitopes (glycotopes). Nevertheless, the biological role of these glycotopes has not been fully evaluated. Recent studies using live cells have begun unraveling the constituents of Siglec ligands. These studies demonstrated that glycoprotein scaffolds (counter-receptors) displaying glycotopes are sometimes just as important as the glycotope itself. These new insights may guide future efforts to develop therapeutic agents to target the Siglec – ligand axis.